Targeted treatments of HER2-positive metastatic breast cancer: trastuzumab and beyond. (September 2012) - Zardavas, Dimitrios; Pugliano, Lina; Ades, Felipe; Bozovic-Spasojevic, Ivana; Capelan, Marta; de Azambuja, Evandro
SUMMARY HER2 positivity defines a molecular subtype of breast cancer with aggressive biological behavior. HER2 has been clinically validated as a prominent therapeutic target in breast cancer, and an abundance of data from clinical trials proving the efficacy of trastuzumab, a humanized anti-HER2 monoclonal antibody, has changed the natural history of this disease. Despite positive results from many trials, resistance to anti-HER2 agents inevitably occurs in both the metastatic and adjuvant settings. This clinical reality has led to the development of various other targeted agents designed to block the HER2 receptor. Similarly, attempts to elucidate the molecular mechanisms of resistance to the already established anti-HER2 agents have opened new therapeutic avenues with numerous promising agents. This review presents a comprehensive overview of the data available on anti-HER2-targeted agents other than trastuzumab, and describes both challenges and directions for the future.